Strategi Pengembangan Industri Kecil Menengah (IKM) Yang Berdaya Saing Pada Saat Covid-19 di Kota Pekanbaru - Rendra Wasnury; Anggia Paramitha; Rika Promalessy (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2022)
The objective of this study is to analyze the main issues that inhibit the development of IKM competitiveness in Pekanbaru City at the time of COVID-19 by identifying the development status of IKM in Pekanbaru City today and the persemade strategy in the midst of the Covid-19 pandemic and the development of IKM competitiveness in Pekanbaru city at the time of covid. According to the data provided by Pekanbaru City Industrial and Trade Bank, the population in this study are all IKMs operating in Pekanbaru City. The IKM that becomes the subject of this study is the IKM of manufacturing or IKM which manufactures products that are able to be competitive in the broad market and become a substitute for consumers in Pekanbaru City. The data analysis used in the IKM study is a descriptive analysis using the SWOT analysis method.The results showed the development of the IKM competitiveness in Pekanbaru city at the time of COVID-19 that was in the 2nd quadrant position. For that, the IKM development model is consistent with the forward, backward and horizontal integration strategy, that is, by strengthening business relationships with upstream and downstream industries, and increasing control over competitors through cooperation and company acquisitions. As for the market penetration strategy or by determining the market's ability to absorb the resulting product. Also, the product development strategy is to develop products with offer value (value proposition) combined with services to enhance the uniqueness of the product, which can help IKM improve marketing performance and market expansion. And keep the market satisfied by opening up new market shares resulting from market development strategies.